2019
DOI: 10.1097/md.0000000000015745
|View full text |Cite
|
Sign up to set email alerts
|

Total knee arthroplasty for a valgus deformity angle of >90°

Abstract: Rationale: Valgus knees are relatively rare in the clinic. Treatments for valgus deviations >90° represent a surgical challenge to achieve a balance between the soft tissue and bone and prevent nerve damage. Patient concerns: A 63-year-old woman with valgus deviations >90° in both knees complained that she had been unable to walk for 50 years. Diagnoses: Congenital malformation valgus deformity. Interventions: Bila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Valgus deformity of the knee is less commonly encountered but more technically challenging than varus deformity 1 . Distal femoral osteotomy (DFO) is predominantly used for mild to moderate valgus deformity, with positive short‐term and long‐term clinical outcomes, and even reduces the need for joint replacement 2,3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Valgus deformity of the knee is less commonly encountered but more technically challenging than varus deformity 1 . Distal femoral osteotomy (DFO) is predominantly used for mild to moderate valgus deformity, with positive short‐term and long‐term clinical outcomes, and even reduces the need for joint replacement 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…Valgus deformity of the knee is less commonly encountered but more technically challenging than varus deformity. 1 Distal femoral osteotomy (DFO) is predominantly used for mild to moderate valgus deformity, with positive short‐term and long‐term clinical outcomes, and even reduces the need for joint replacement. 2 , 3 It has also been demonstrated that restoration of the biomechanical axis reduces the levels of inflammatory factors within the knee joint, which could provide a favorable environment for cartilage regeneration.…”
Section: Introductionmentioning
confidence: 99%